2008
DOI: 10.1073/pnas.0711629105
|View full text |Cite
|
Sign up to set email alerts
|

A vaccine strategy against AIDS: An HIV gp41 peptide immunization prevents NKp44L expression and CD4 + T cell depletion in SHIV-infected macaques

Abstract: We previously showed that a gp41 peptide (3S) induces expression of a natural killer (NK) ligand (NKp44L) on CD4 ؉ T cells during HIV-1 infection and that those cells are highly sensitive to NK lysis. In HIV-infected patients, anti-3S antibodies are associated with the maintenance of CD4 ؉ T cell counts close to their baseline values, and CD4 ؉ T cells decrease with the antibody titer. This study sought to determine whether anti-3S immunization could prevent NKp44L expression on these CD4 ؉ T cells in vivo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
3
36
0
2
Order By: Relevance
“…A recent report showed that immunization against the 3S gp41 peptide prevents the expression of the NKp44 ligand on CD4 pos T cells, thus lowering the depletion of these cells in a model of SHIV-infected primates. These results provide new insight to possibly develop alternative preventive and therapeutic HIV-1 vaccine strategies [106]. However, recent results from the same group showed unexplained differences between R5 and X4 infection [107].…”
Section: Immunomodulatory Hiv-1 Targeting Of Nkr Ligandsmentioning
confidence: 94%
“…A recent report showed that immunization against the 3S gp41 peptide prevents the expression of the NKp44 ligand on CD4 pos T cells, thus lowering the depletion of these cells in a model of SHIV-infected primates. These results provide new insight to possibly develop alternative preventive and therapeutic HIV-1 vaccine strategies [106]. However, recent results from the same group showed unexplained differences between R5 and X4 infection [107].…”
Section: Immunomodulatory Hiv-1 Targeting Of Nkr Ligandsmentioning
confidence: 94%
“…37 We previously reported that NKp44L is also expressed on bystander uninfected CD4 1 T cells from HIVinfected patients. [20][21][22]38 In these CD4 1 T cells, the cell-surface translocation of NKp44L is mediated through a signaling cascade that involves sequential activation of PI3K, and NADPH oxidase, as well as TC10 inactivation. 39 Saliently, MLL5 has been described as a nuclear protein, 28 whereas NKp44L is not found in the nucleus, consistently with data of Madrid and Ganem.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The cellular ligand of NKp44, called natural cytotoxicity receptor NKp44 (NKp44L), is expressed on CD4 1 T cells during HIV infection, 20,21 and its expression is correlated with the decline of the CD4 1 T-cell count, both ex vivo in HIV-infected patients, 20 and in vivo in SHIV-infected macaques. 22 To better understand the relations between NKp44 and the pathophysiology of both infectious diseases and malignancies, we undertook studies to identify and characterize its cellular ligand (NKp44L). Here, we found that NKp44L is an isoform of mixed-lineage leukemia-5 (MLL5), located in the human chromosome band 7q22.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of NKp44L is triggered by the 3S conserved motif in gp41env, and can readily be prevented by immunization with a 3S peptide, as shown in non-human primates. Thus, a vaccine based on a 3S peptide coupled to KLH blocked expression of the NKp44L signal on bystander CD4 + T cells in SHIV-infected rhesus macaques and prevented the NK cell-mediated T CM cell depletion that characterizes SIV and HIV infections [31,32]. Furthermore, a specific mutation at site W614 in 3S generated a peptide that induced Abs able to neutralize HIV-1 infectivity cross-clade while at the same time protecting CD4 + T cells against NK cell killing.…”
Section: Novel Approachesmentioning
confidence: 94%